Alternative tax-benefit strategies to support children in Poland - Horacio Levy; Leszek Morawski; Michal Myck (University of Essex, Institute for Social and Economic Research (ISER), 2008)
Eurostat data shows that children and elderly are especially at risk of being in poverty. In 2004 the average rates of poverty risk in the European Union for these groups were about 19%. In Poland, the rate was 29% for children and only 7% for the elderly. We examine the role of the tax-benefit system in explaining this situation and analyse how much child poverty figures could change under several reform scenarios. In 2005, families with children were mainly supported by a means-tested family allowance and some supplements. This was extended in 2007 with the introduction of a non-refundable child tax credit. Making use of the European tax-benefit microsimulation model EUROMOD, this paper assesses the consequences of the recent reform in Poland. We examine the outcome in comparison to child policies in three other European systems and show that poverty reduction would have been more pronounced, if child policies were changed along the lines of the system in France or the United Kingdom. The Austrian system - relying primarily on universal benefits - would bring about a similar reduction in the poverty rate but with much greater reduction in the poverty gap. The paper presents detailed distributional analysis under the different systems assuming the cost of importing each of them to be the same as that of introducing the 2007 reform.
Keywords: D31; I38; 330; child poverty; tax and benefit reforms; transition; Familienleistungsausgleich; Kinder; Polen